Al-WĀQI ‘AL-IJTIMĀ’IYYAH IN THE REVIEW OF THE QUR’AN (ISLAMIC LAW) - Abidin Abidin (State Institute of Islamic Studies (IAIN) Palu, 2018)
This paper will discuss about al-Wāqi’ al-Ijtimā’iyyah review of Islamic law. The main problem is how al-Wāqi’ al-Ijtimā’iyyah views Islamic law. The subject matter is formulated into the sub-issue of how the nature of al-Wāqi’ al-Ijtimā’iyyah is. The approach method used in analyzing this sub-issue is the qualitative and descriptive approach of Islamic law and term. The goal to be achieved in this paper is to know the nature of al-Wāqi’ al-Ijtimā’iyyah. From the data obtained can be concluded that the nature of al-Wāqi’ al-Ijtimā’iyyah is a social fact that contains real events that actually exist or occur as a result of human interaction with other human beings, good or bad, empirical or idea, written (text) or habits (contextual), both that happened in the past and now associated with Islamic law in the sense of jurisprudence is not a worship whose nasal passages ẓannī al-dalālah and qaṭ’ī al-dalālah.